Solidus Temperature in Optimization and Prediction of Alloy Mild Steel in Tungsten Inert Gas Weldment - A. O. Igbinake; C. O. Aliyegbenoma (Journal of Applied Sciences and Environmental Management)
Solidus temperature indicates the temperature at which an alloy is completely solid it is considered as an important parameters of alloy in Tungsten Inert Gas (TIG) welding. Therefore, the objective of this paper was to investigate the solidus temperature in the optimization and prediction of alloy mild steel in Tungsten Inert Gas (TIG) weldment using response surface methodology and other appropriate standard procedures. Data obtained show that The result from the response surface methodology shows that a combination of current of 180A, voltage 19V, gas flow rate 13L/min, l produce optimal solidus temperature of 1278.00oC and a desirability of 91.5%. The developed model would minimize solidus temperature.